Seasonal Variation of Heavy Metals in Industrial Soils: Assessment Using Contamination Factor, Pollution Load Index and Geoaccumulation Index - Dogra, Preeti; Kumar, Prashant (International Journal of Aquatic Research and Environmental Studies, 2026)
Heavy metal contamination in industrial soils is a persistent environmental concern because metals are non-biodegradable, toxic, and capable of accumulating in soil systems over long periods. Seasonal processes such as rainfall, runoff, leaching, and atmospheric deposition may influence the distribution and pollution intensity of metals in soil. This study assessed seasonal variation of copper (Cu), lead (Pb), nickel (Ni), and zinc (Zn) in industrial soils of Jammu City during pre monsoon and post-monsoon seasons. Soil samples were collected from six selected industrial sites and analyzed using Atomic Absorption Spectrophotometry. Contamination Factor (CF), Pollution Load Index (PLI), and Geoaccumulation Index (Igeo) were used to evaluate contamination status, while Wilcoxon signed-rank test, Spearman correlation, and Principal Component Analysis were applied for statistical interpretation. Zn showed the highest concentration in both seasons, followed by Cu, Pb, and Ni. CF values exceeded 6 for all metals, indicating very high contamination. PLI values were 9.00 and 8.84 during pre-monsoon and post-monsoon seasons, respectively, indicating progressive pollution. Mean Igeo values indicated moderate to heavy pollution. Although seasonal variations were observed, they were not statistically significant. The findings suggest persistent industrial soil contamination in Jammu City, mainly associated with anthropogenic activities, highlighting the need for regular monitoring and remediation.